Electron and Ion Transport of Tin Dioxide in Secondary Batteries: Enhancement Approaches, Mechanisms, and Performance - Han, Tianli; Qi, Mingqiang; Yang, Shanshan; Diao, Xinya; Long, Jiawei; Zhu, Mengfei; Xu, Xiaoyong; Hu, Chaoquan; Liu, Jinyun (Frontiers in Physics, 2021)
Secondary batteries have been of importance for several fields in daily life and industrial manufacture. The electron and ion transport of electrodes significantly affect the energy-storage performance of the batteries. Among many fascinating materials, transition metal oxides have been considered promising as candidate electrode materials of high-performance batteries owing to their high theoretical capacity and good stability. Herein, tin dioxide is chosen as a representative transition metal oxide to show the specific electron and ion transport in some types of secondary batteries including lithium-ion, lithium-sulfur, potassium-ion batteries, etc. The way to optimize the structure, and the strategies to enhance the electron and ion transport have been summarized. Recently, doping towards tin dioxide and the preparation of tin dioxide-based composites have been reported. In addition, the main challenges and possible prospects are also proposed, which provide important suggestions for researchers to develop high-performance energy-storage materials and to explore new physic science.